Vehicle yaw stability control via H∞ gain scheduling. (June 2018) - Zhang, Jinhua; Sun, Weichao; Feng, Zhiguang
Highlights: Development of a LFT H ∞ gain scheduling model for vehicle yaw stability control. Construction of a H ∞ gain scheduling controller under the parameter. perturbations of vehicle mass and moment of inertia. Verification of the designed controller via numerical and MATLAB-CarSim coalition simulation. Abstract: Yaw stability control (YSC) is rather significant in a vehicle lateral motion, since it can considerably reduce casualties caused by vehicle instability. Nevertheless with the vehicle running, the parameters, such as vehicle mass and moment of inertial, can be perturbed because of variation of capacity, loadage and consumption of fuel, hence some of nominal controllers cannot always work satisfactorily. To overcome the aforementioned deficiency, a gain scheduled H ∞ YSC controller is developed in this paper, taking the vehicle mass and moment of inertial as the scheduled variables, now that the gain scheduled H ∞ controller can guarantee both the robustness against parameter perturbation and the adjustability of tracking accuracy. Then the constructed controller is verified via numerical simulation and MATLAB-CarSim coalition simulation. The simulation results indicate that the designed controller can indeed improve the vehicle handing performance under circumstance of lateral stability.